2011
DOI: 10.1007/s11119-011-9254-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability in grape yield and quality influenced by soil and crop nutrition characteristics

Abstract: Knowledge of spatial variability of soil fertility and plant nutrition is critical for planning and implementing site specific vineyard management. To better understand the key drivers behind vineyard variability, yield mapping from 2002 to 2005 and 2007 (the monitor broke down in 2006) was used to identify zones of different productive potential in a Pinot Noir field located in Raimat (Lleida, Spain). Simultaneously, the vineyard field was sampled in 2002, 2003 and 2007, applying three different schemes (depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 11 publications
2
47
0
Order By: Relevance
“…It has been shown that vegetative and soil parameters show a positive spatial autocorrelation, as points close to each other have similar values (Arnó, Rosell, Blanco, Ramos, & Martínez-Casasnovas, 2011;Baluja, Diago, Goovaerts, & Tardaguila, 2012;Tardaguila, Baluja, Arpon, Balda, & Oliveira, 2011). This leads to the idea of using local autocorrelation coefficients, such as the Moran local index, or locally weighted regressions to improve missing plant detectability, as proposed for spatial data analysis by Shekhar, Lu, and Zhang (2003) and Anselin, Syabri and Kho (2006).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that vegetative and soil parameters show a positive spatial autocorrelation, as points close to each other have similar values (Arnó, Rosell, Blanco, Ramos, & Martínez-Casasnovas, 2011;Baluja, Diago, Goovaerts, & Tardaguila, 2012;Tardaguila, Baluja, Arpon, Balda, & Oliveira, 2011). This leads to the idea of using local autocorrelation coefficients, such as the Moran local index, or locally weighted regressions to improve missing plant detectability, as proposed for spatial data analysis by Shekhar, Lu, and Zhang (2003) and Anselin, Syabri and Kho (2006).…”
Section: Introductionmentioning
confidence: 99%
“…Among others, Gil-Perez et al (2010), Tardaguila et al (2011) and Arnó et al (2012) have recently pointed out the great importance of soil fertility, soil depth, as well as the mineral petiole concentration for producing high quality wines.…”
Section: Discussionmentioning
confidence: 99%
“…Vineyard soils are the substrate for cultivated grapevines; they allocate moisture and nutrient uptake, influence the microclimate in the canopy and have an impact on the typicity of the wine (Bramley et al 2011a, Jackson and Lombard 1993, Schultz and Löhnertz 2002, Meggio et al 2010, Bramley et al 2011a, Bramley et al 2011b, Tardaguila et al 2011, Arnó et al 2012, Hall and Wilson 2013. Thus, soil management has a direct influence on grape vegetative growth, fruit composition, and finally wine quality.…”
Section: Introductionmentioning
confidence: 99%
“…2). Most of the published research has been carried out on the within-field scale in the context of the so-called "site-specific" or "precision viticulture" (Bramley and Hamilton, 2004;Bramley, 2005;Bramley et al, 2011a, b, c, d, e;Tisseyre and McBratney, 2008;Roudier et al, 2008Roudier et al, , 2011Arnó et al, 2009Arnó et al, , 2012Pedroso et al, 2010), and its median study area covered only 0.12 ha, while between-field studies covering more than 0.11 km 2 only represented a quarter of the total (Fig. 3).…”
Section: General Perspectivesmentioning
confidence: 99%
“…According to farmers, a model should be capable of predicting water stress at least 2 weeks before severe irreversible water stress damage occurs (J. C. Viaud, personal communication, 2014). Arnó et al (2012) stated that overall within-field variability of grape yield and quality raises important questions concerning whether site-specific crop management could be used in vineyards. Problems arise, in particular, when looking for causes of this variability, especially those related to the presence of soil carbonates, which may lead to Mn deficiencies, with deleterious effects on grape colour.…”
Section: The Issue Of Big-data Handling and The Statistical Processinmentioning
confidence: 99%